Mini IR Radar for Unauthorized Object Detection - Pandey, Tanya; Mishra, BP (Journal of Advanced Research in Instrumentation and Control Engineering; Vol 7 No 1 (2020): Journal of Advanced Research in Instrumentation and Control Engineering(ISSN: 2456-1398), 2021)
The purpose of this paper is to present Mini IR Radar for unauthorized object detection using IR sensor.   More precise definition of radar is that it is a system used for recognition of target objects by transmitting IR signal, receiving reflection from target objects within its volume of coverage and extracting information such as distance and angle. The system can monitor an area of limited range and alert the authorities with a buzzer and LCD screen for monitoring a PIC controller circuit that is connected to an IR sensor mounted on a stepper motor for the detection status. As soon as an object is detected the radar system will detect the distance as well as the angle and display it on the LCD screen. After detecting that particular object after certain time span the motor will continue to rotate till next object is detected . How to cite this article: Mishra BP, Pandey T, Jha S et al. Mini IR Radar for Unauthorised Object Detection. J Adv Res Instru Control Engg 2020; 7(1): 9-11.